Experimental and numerical study on phase change material (PCM) for thermal management of mobile devices. (5th April 2016) - Tomizawa, Yusuke; Sasaki, Katsuhiko; Kuroda, Akiyoshi; Takeda, Ryo; Kaito, Yoshihiko
Highlights: ⋅ PCM sheets are effective in temperature change within a smart phone simulator. ⋅ Temperature increasing rate decreases with an increase in mass of PCM sheets. ⋅ Thicker PCM sheets are more effective for delaying the temperature increase rate. ⋅ PCM sheets lined with high thermal conductivity materials lead to low temperature. ⋅ Typical estimation of thermophysical properties can be adapted to PCM sheets. Abstract: As mobile devices become more complex and higher in performance despite the smaller size, heat concentration at localized areas has become a problem. In recent years, passive cooling using phase change materials (PCMs) has drawn attention as a thermal management method for mobile devices. PCMs reduce the temperature increase rate due to their latent heat properties. This reduction in the temperature increase rate is called a "delay effect". Moreover, microencapsulated PCMs (MPCMs) are attracting attention because they keep the melted PCMs from leaking. In this study, PCM sheets containing MPCM/polyethylene composite material are investigated for the thermal management of mobile devices. Namely the authors conduct a series of experiments using the PCM sheet with a high thermal conductivity sheet mounted into a simply modeled mobile device. Effects of the mass, the latent heat, the thermal conductivity, the configuration of the PCM sheet, and high thermal conductivity sheet on the temperature of a smart phone simulator are investigated. A finite element analysis (FEA) is also conducted considering the phase change of PCMs to investigate the optimal dimension and shape of PCMs. As a result, the delay effect of PCMs and the effectivity of a copper sheet pasted on the PCMs are verified by experiments. Moreover, FEA shows that using the PCM sheet with high thermal conductivity sheet has an advantage for the thermal management of mobile devices and gives an optimal condition for the PCM sheets.